Exploratory Analysis of Educational Ecosystem Factors Affecting the Learning Diligence - Elok Hidayah; Aminatur Rosyidah; Izza Afkarina (Jurnal Cakrawala Pendidikan dan Biologi, 2025)
Recent declines in student ethics and learning diligence indicate deeper systemic challenges within the contemporary educational ecosystem. This situation prompts critical inquiry into the respective contributions of school governance, teacher practices, and familial environments in shaping student’s learning orientations. This study seeks to identify the principal determinants of learning diligence from the perspectives of teachers, parents, and students, employing a qualitative exploratory–interpretive design. Data were elicited through narrative stimuli intended to provoke reflective and affectively grounded responses, which were subsequently examined using inductive–thematic analysis. The findings demonstrate that structural weaknesses within school systems, particularly ambiguous policy direction, inconsistent institutional regulations, and ineffective evaluative mechanisms—constitute dominant factors undermining student’s motivation and academic discipline. Parental influences also play a substantive role; insufficient parental engagement and inadequate developmental guidance contribute to weakened responsibility and diminished learner commitment. Some students report withdrawing from academic engagement due to unclear expectations and the absence of supportive school conditions. Moreover, perceptions of automatic grade promotion and guaranteed graduation exacerbate motivational decline. Collectively, these findings indicate that learning diligence emerges from a complex interplay between institutional structures, pedagogical practices, family dynamics, and student’s psychosocial conditions. Addressing these issues thus requires coordinated, systemic, and multi-stakeholder intervention.